Multibeam Crosscheck Analysis A Case Study - Eeg, Jørgen (The International Hydrographic Review, 2010)
A new method for analyzing overlapping areas in multibeam surveys is introduced. The method requires that the velocity of sound in the water at the transducer is monitored during the survey. The method applies the principle of least squares to determine the vertical offset and the bias of the swaths caused by insufficient knowledge of the velocity of sound in the water column below the transducer. The precision and robustness of the method is demonstrated on a survey.